2016
DOI: 10.1186/s12889-016-3575-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of tuberculosis from 2002 to 2012 in a midsize city in Brazil

Abstract: BackgroundTuberculosis (TB) remains a major public health problem in many developing countries. Exploratory spatial analysis is a powerful instrument in spatial health research by virtue of its capacity to map disease distribution and associated risk factors at the population level. The aim of the present study was to describe the epidemiologic characteristics and spatial distribution of new cases of TB reported during the period 2002–2012 in Divinopolis, a midsized city located in the state of Minas Gerais, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
1
7
3
2
Order By: Relevance
“…The research of [56] stated that the spatial distribution of TB was more concentrated in neighborhoods with higher population and intradomiciliary densities, corroborating the results of the present study. Another study found that TB occurred predominantly in the central region of Divinópolis, Minas Gerais, Brazil, and a significant association can be found between the disease and the sites with the highest population density [49], similarly to the findings of this work. In a study conducted in Fortaleza, Brazil, it was found that TB cases were agglomerated in areas with high informal settlement rates [57].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The research of [56] stated that the spatial distribution of TB was more concentrated in neighborhoods with higher population and intradomiciliary densities, corroborating the results of the present study. Another study found that TB occurred predominantly in the central region of Divinópolis, Minas Gerais, Brazil, and a significant association can be found between the disease and the sites with the highest population density [49], similarly to the findings of this work. In a study conducted in Fortaleza, Brazil, it was found that TB cases were agglomerated in areas with high informal settlement rates [57].…”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, the rules that make up each rule-based fuzzy system within each SDSS should also be changed. Studies show that TB is more frequent in males individuals [46–49], perhaps as a result of men being more prone to alcoholism, malnourishment or co-infection with the HIV virus [50]. Regarding the educational level, investigations show association of TB with illiteracy and low level of schooling [50, 51].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that serum albumin level, high population density and healthcare worker were associated with TB. 20,21,22 Those results may be due to malnutrition, higher exposure to TB patients and overcrowding. However, those results could also be related to any potential bias, such as selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…9 Relations evidenced by the inverse association between the socioeconomic status and TB incidence, relation between vulnerability, socioeconomic and sociodemographic condition, mortality and coinfection by HIV-TB. [10][11][12][13][14][15][16][17][18][19][20][21] The vulnerability was also observed among indigenous people, in the data of child mortality due to HIV-TB coinfection, being 3 times higher in orphan children, along with in the difficult adherence to the TB treatment and poor living conditions of people subjected to such circumstances. [22][23][24]…”
Section: Social Determinantsmentioning
confidence: 99%